Molecular Docking of Mangostin and Sinensetin Derivatives on SUR1-Pancreatic KATP Channel Target as Antidiabetic - Intan Kris Prasetyanti; Sukardiman Sukardiman; Suharjono Suharjono (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2021)
Background: Diabetes Mellitus (DM) is a complex chronic disease characterized by increased blood glucose. The incidence of this disease is rising, especially type 2 diabetes which is caused by insulin resistance in the body. SUR1-Pancreatic KATP Channel is a receptor as an antidiabetic target because its inhibition process can increase insulin production so that it can reduce blood glucose in people with type 2 diabetes. Objective: This study aims to identify the in-silico activity of the SUR1-Pancreatic KATP Channel macromolecules. Methods: Identification of macromolecular binding sites using Protein Plus software, then carried out molecular docking using AutoDock software, where the formed molecular interactions are further identified using the BIOVIA Discovery Studio software. Results: After determining the macromolecular binding site, the RMSD value was 1.253, allowing for further molecular docking. Molecular docking showed that the Ligands of mangostin (α, β, Î³-mangostin) and sinensetin derivatives had a good affinity, namely α-mangostin -6,31 kcal/mol; β-mangostin -5.78 kcal/mol; Î³-mangostin -6.17 kcal/mol and sinensetin -4.75 kcal/mol. Conclusion: The affinity sequence in the docking process for the SUR1 KATP channel macromolecules is α-mangostin > Î³-mangostin > β-mangostin > sinensetin. The highest affinity for the docking process on the macromolecule SUR1 KATP channel was α-mangostin with a value of Î”G -6.31 kcal/mol Ki 23.65 Î¼M.